Glyphosate residues in coffee bean: Impact of application methods and compliance with MRLs - Foloni, Luiz L.; Velini, Edivaldo D. [UNESP]; Carbonari, Caio A. [UNESP]; Rodrígues, João D. [UNESP]; Ono, Elizabeth O. [UNESP]; Alcántara-De la Cruz, Ricardo (Advances in Weed Science, 2024)
Background: Farmers often use glyphosate for cost-effective land clearance to streamline coffee harvest processes despite recommendations against its application near the harvest period. However, as set by national and international regulatory authorities, this practice poses a high risk of exceeding the maximum residue limit (MRL) for glyphosate in coffee beans. Objective: In this study, glyphosate residues in green coffee beans were assessed, considering different herbicide application methods (mechanical or manual), nozzles (hooded or unhooded), application volumes, and ripening stages. Methods: Coffee beans were collected between 15 to 60 days before harvest, and glyphosate residues were determined by highefficiency liquid chromatography and mass spectrometry (LC-MS/MS). Results: Mechanical and manual applications using a protective spray bar device, avoiding the lower third of the coffee trees, maintained glyphosate residue levels within the MRLs established by Brazilian (1.0 mg kg–1) and European (0.1 mg kg–1) regulatory authorities. In contrast, applying glyphosate with the TK-VS-02 nozzle (high-flow impact) without a protective device resulted in levels below the Brazilian MRL but exceeded importing countries’ requirements. These residue levels persisted even when applications occurred outside the recommended rainy season but within the 15-day minimum safe re-entry interval. Applications using TK-VS-02 or AI11002 (low-flow air-induced) nozzles targeting the lower third of trees resulted in high glyphosate residue levels, surpassing national and international MRLs, even when applications were conducted 60 days before coffee harvest. Conclusions: These findings emphasize the importance of employing the right application technology to produce coffee that complies with the MRLs of any regulatory authority.
Keywords: Coffee Harvest; Global Coffee Platform; Hooded Nozzle; Maximum Residue Limit; Regulatory Authorities; Safe Re-entry Interval